SERVICE QUALITY DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Sony Novian; Aam Bastaman (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of Service Quality and Brand Image on Repurchase Intention with Customer Satisfaction as an intervening variable at Katagonia Language Solutions. The background of this research reflects the intense competition in the language services industry, where retaining customers depends on service quality, a strong brand image, and customer satisfaction. The method used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0. Data were collected from 200 respondents using purposive sampling. The results show that Service Quality has a positive and significant effect on Repurchase Intention, but does not significantly affect Customer Satisfaction. Meanwhile, Brand Image was found to significantly affect both Customer Satisfaction and Repurchase Intention, and became a dominant factor in building customer loyalty. Customer Satisfaction also significantly affects Repurchase Intention, strengthening long-term customer relationships. Mediation analysis shows that Customer Satisfaction plays a significant role as a link between Brand Image and Repurchase Intention, but not between Service Quality and Repurchase Intention. These findings suggest that Katagonia should focus more on strengthening its brand image and creating a satisfying customer experience. This strategy is expected to increase customer loyalty and strengthen Katagonia’s position in the competitive language services market.